3x+12=6x+23

Simple and best practice solution for 3x+12=6x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+12=6x+23 equation:



3x+12=6x+23
We move all terms to the left:
3x+12-(6x+23)=0
We get rid of parentheses
3x-6x-23+12=0
We add all the numbers together, and all the variables
-3x-11=0
We move all terms containing x to the left, all other terms to the right
-3x=11
x=11/-3
x=-3+2/3

See similar equations:

| 6x+104=16x+-114 | | v²+30=-11v | | 25a²=9 | | 27100=12500(1+0,35)n | | 25a²=19 | | 3/8x+2=5/12-4x | | -6(1-8b=-246 | | 25a²+5=14 | | 8(t-4)+4t=4(3t+4)-12 | | 14x+5=69 | | 4(8^(8^x)=-11(8^4x)+20 | | 5+7x-4=9x+33-6x | | -2×+4z=2.16 | | x^2-60=6x | | 36/30=n/5 | | x-36=-23+47 | | 15x^2-x+84=0 | | 3(x-6)=6x+24. | | x/3+3/3=15/4 | | -2.3y=-0.7y+4.8 | | 2+19p-24=-22 | | t^2+13t+8=0 | | x-14=52-21 | | x^2-7.46x-45=0 | | x^2=7.46x-45=0 | | 24x=2980 | | 4/3x+7/6x=48/9 | | x+54=21 | | 8x-5=-9x+3 | | 6a-14=4a+2 | | 3x-9+4x-3=180 | | -16x+5=-22x+8 |

Equations solver categories